The Effect Of Employee Welfare, Work Environment, And Interpersonal Relationships On The Work Productivity Of Employees At Pt. Bumi Anugerah Sawit Bengkulu Utara - Alamsyah, Alif Novliyan; Irwanto, Tito; Subhi, Ramadan (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2026)
Employee work productivity is an important factor for the success of the company. PT. Bumi Anugerah Sawit faces challenges in maintaining productivity amidst high work demands, so it requires attention to employee welfare, work environment, and interpersonal relationships. This study aims to analyze the influence of employee welfare, work environment, and interpersonal relationships on employee work productivity at PT. Bumi Anugerah Sawit Bengkulu Utara. The research method uses a quantitative approach with 40 respondents, and the data are analyzed through validity and reliability tests, multiple linear regression, t-test, F-test, and coefficient of determination (R²) using SPSS version 26. The results show that employee welfare (X₁), work environment (X₂), and interpersonal relationships (X₃) have a positive and significant effect on employee work productivity (Y), both partially and simultaneously. The calculated F value of 1041.083> Ftable 2.86 and a significance of 0.000 <0.05, indicating a joint influence between the three independent variables on work productivity. The coefficient of determination (R²) value of 0.843 means that 84.3% of the variation in work productivity can be explained by these three variables, while the remaining 15.7% is influenced by other factors outside the study. Thus, it can be concluded that improving welfare, creating a good work environment, and harmonious interpersonal relationships play an important role in increasing employee work productivity at PT. Bumi Anugerah Sawit Bengkulu Utara.